High-Fish Oil and High-Lard Diets Differently Affect Testicular Antioxidant Defense and Mitochondrial Fusion/Fission Balance in Male Wistar Rats: Potential Protective Effect of ω3 Polyunsaturated Fatty Acids Targeting Mitochondria Dynamics - Vincenzo Migliaccio (International Journal of Molecular Sciences, 2019)
High-fat diets rich in fish oil (HFO diet, mainly ω3-PUFAs), in contrast to high-fat diets rich in lard (HL diet, mainly saturated fatty acids) have been shown to induce improvement in mitochondrial function and fusion processes associated with a reduction in reactive oxygen species production in both liver and skeletal muscle. High-fat diets may also impair testicular function, and mitochondria represent important cellular organelles with a pivotal role in reproductive function. Mitochondria are dynamic organelles that frequently undergo fission/fusion processes. A shift toward mitochondrial fusion process has been associated with improvement of mitochondrial function, as well as with ω3-PUFAs protective effects. The present study aimed to analyze the effect of chronic overfeeding (six weeks) with HFO or HL diet on testicular tissue histology, oxidative stress, antioxidant defenses, and mitochondrial fusion (mitofusin 2) and fission (dynamic related protein 1) protein. Our results showed that HFO diet induced less testicular histology impairment, oxidative stress, and apoptosis compared to a HL diet. This finding was associated with an increase in antioxidant activities and a shift toward mitochondrial fusion processes induced by HFO diet compared to HL diet, suggesting that ω3-PUFAs may act as bioactive compound targeting mitochondria dynamics to prevent testicular impairment.